PEMANFAATAN KEANEKARAGAMAN GENETIK TUMBUHAN OLEH MASYARAKAT TUGUTIL DI SEKITAR TAMAN NASIONAL AKETAJAWE LOLOBATA (Utilization of Plant Genetic Biodiversity by Tugutil tribe in Aketajawe Lolobata National Park) - Kartini Abd. Karim; Machmud Thohari; . Sumardjo (Media Konservasi, 2006)
Indonesia is one of the richnest country in biodiversity, including the higest of diversity of agriculture genetic resources. Tugutil society is one ethnic in halmahera which have well knowledges in used of genetic resouces. Indigenous knowledges on genetic resources of agriculture by tugutil in Wasile, Halmahera is presented. 149 sources of They have been used 149 agricultural and medicinal genetic resources. There are 100 genetic resources of agriculture crop (71 species) they used for sources of primary food, secondary food like fruit, vegetables, etc.) and 49 plant medicinal genetic resources (45 species). Tugutil society has knowledge about how they wise used the genetic resources like not over exploited, local wisdom to conservation their genetic resources from destruction.